Hubungan Antara Gaya Kelekatan Dewasa Dengan Toxic Relationship Pada Mahasiswa Bimbingan dan Konseling yang Berpacaran - Hanindya Putri Dewanti; Dendy Setyadi (Lembag, 2024)
This study is a correlational quantitative research. The study aims to find out the relationship between adult attachment style and toxic relationship in dating Guidance and Counseling students and to find out how high the level of adult attachment style and toxic relationship level in dating Guidance and Counseling students. The subjects totaled 102 students. Data collection used the adult attachment style scale with 62 valid items with a reliability test value of 0.971 and the toxic relationship scale with 37 valid items with a reliability test score of 0.999. The results showed that there was a negative relationship between adult attachment style and toxic relationship with a high level of significance with a value of r -0.712 and p < .001. The level of adult attachment style of dating students is classified as high with a percentage of 43%. The level of toxic relationships in students who are dating is classified as low with a percentage of 52%. Based on these results, it can be seen that the higher the level of adult attachment style, the level of toxic relationships tends to decrease, and vice versa